The concept of naṣīḥah as the philosophy of Islamic spiritual care - Jamil, Khairil Husaini (Department of Qurʾan and Sunnah Studies, 2022)
This paper proposes the Islamic concept of naṣīḥah as the core concept for the philosophy of Islamic spirituality and by extension Islamic spiritual care. Naṣīḥah in this context is not treated as merely verbal advice, rather it is elaborated in such a way that it covers the actualisation of the tawḥidic paradigm, and methodologically, as permitted by its semantic, embraces synthesis, integration, purification, filtering, relevantisation as well as Islamisation or Islamicisation. Hence, naṣīḥah represents the crux of religion and the raison d’etre of Islam as declared by the Prophetic ḥadīth. The paper discusses its postulation by addressing two main concepts: first, al-riʿāyah as the idea of Islamic spiritual care, second, naṣīḥah as the conceptual framework of al-riʿāyah. Its arguments are based mainly on the interpretation of related Qurʾānic verses, Prophetic ḥadīths and the Islamic intellectual tradition. The paper concludes that naṣīḥah suits as a unifying concept, moreover if appreciated as a key philosophical and civilisational concept of the Islamic worldview.